Morphometry of the inferior articular facet of the atlas - Neeru Goyal; Anjali Jain (Wolters Kluwer Medknow Publications, 2021)
Objectives: Atlas and axis vertebrae have unique anatomical features compared to the rest of the cervical vertebrae. Variations of superior articular facet of the atlas have been extensively described. However, only limited studies describe the variations of the inferior articular facet. The aim of the present study is to explore the variations in the shape, size, and symmetry of the inferior articular facet of the atlas. Materials and Methods: The study was conducted on 110 dried adult atlas vertebrae. Shape, size, and the number of the inferior articular facets on each atlas were recorded. Results: Different shapes observed include round (36.36%), pear or drop shaped (35.09%), oval (21.36%), rectangular (3.6%), and triangular (3.0%). Nearly 87.73% facets were flat, whereas 12.27% were concave. In 43.64% of cases, the shape of the inferior articular facet was found to be different on the two sides of the same vertebra. Conclusions: Although not many authors have described the shape of the inferior articular facet, its dimensions have been given by many of them. These dimensions could be helpful while planning and designing implants, etc.